2013
DOI: 10.2147/opth.s44884
|View full text |Cite
|
Sign up to set email alerts
|

Changes in axial length and choroidal thickness after intraocular pressure reduction resulting from trabeculectomy

Abstract: PurposeTo evaluate changes in axial length and choroidal thickness after trabeculectomy.Patients and methodsFourteen patients under 80 years of age with glaucoma, were enrolled. The choroid was imaged using prototypical high-penetration optic coherence tomography (OCT) and the thickness was measured. Axial length, choroidal thickness, and intraocular pressure (IOP) were measured bilaterally at 3 pm 1 day before and 6 days after trabeculectomy. The choroidal thickness was measured at the fovea and four other lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 37 publications
10
56
1
1
Order By: Relevance
“…Accordingly, the reduction in OR observed following IPI implantation in the present study may represent a favorable effect of IPI implantation. Alterations in choroidal circulation or ocular wall structure may explain such OR changes, which have also been reported following other anti-glaucomatous procedures (21,22). Although traditionally AO has been assessed in vivo using tonography or fluorophotometry, the manometric assessment with the methodology described in this study has also resulted in valid results (23).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Accordingly, the reduction in OR observed following IPI implantation in the present study may represent a favorable effect of IPI implantation. Alterations in choroidal circulation or ocular wall structure may explain such OR changes, which have also been reported following other anti-glaucomatous procedures (21,22). Although traditionally AO has been assessed in vivo using tonography or fluorophotometry, the manometric assessment with the methodology described in this study has also resulted in valid results (23).…”
Section: Discussionsupporting
confidence: 57%
“…OR refers to the mathematical relation between the intraocular volume and pressure (expressed by an OR coefficient) and it is considered an important index of the bio-mechanical behaviour of the ocular tissues (21). Changes in OR may play a role in the pathogenesis of glaucoma through alteration in scleral elastic properties (especially in the area of the lamina cribrosa) in different IOP levels (22). An increase in the OR coefficient after prolonged IOP increase has also been documented in animal studies, in rabbits (24).…”
Section: Discussionmentioning
confidence: 94%
“…5 In previous studies, CT has been associated with many factors, such as older age, AL, and IOP; however, the degree of glaucoma damage has not been consistently associated with CT. 7,19,20 There is some controversy regarding the effect of trabeculectomy on CT. Kara et al 17 reported that a large decrease in IOP after trabeculectomy could cause choroidal thickening and that CT changes are associated with AL reduction in POAG. However, Usui et al 21 reported that 6 days after trabeculectomy, the choroid was thicker, the axial length was shorter, and the IOP was lower, but the change in IOP was not correlated with the change in CT at the fovea in POAG. In our study, CT was not related to AL or IOP after trabeculectomy in PACG patients; those results are consistent with the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, IOP level may influence choroidal thickness as it has been shown in the past. 11 In our study, to eliminate the effects of IOP level over the choroidal thickness; participants with IOP level 422 mm Hg were not included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they had a history of ocular surface disorder; any type of glaucoma; previous ocular surgery or injury; history of any systemic disease that may affect the choroidal circulation, such as hypertension, diabetes, vasculitis, or renal failure; or if they were being administered drugs, including analgesics, decongestants, and antihistamines. As choroial thickness is strongly correlated with IOP, refractive error, and axial length; 10,11 to minimize the effect of axial length and IOP on choroidal thickness, patients with best-corrected visual acuity worse than 20/20, a refractive error higher than 1D and the IOP level 422 mm Hg were excluded from the study. All patients underwent a complete ocular examination conducted by the same ophthalmologist (FCE).…”
Section: Methodsmentioning
confidence: 99%